2017
DOI: 10.1007/978-3-319-48382-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance, Obesity and Lipotoxicity

Abstract: Lipotoxicity , originally used to describe the destructive effects of excess fat accumulation on glucose metabolism, causes functional impairments in several metabolic pathways, both in adipose tissue and peripheral organs, like liver, heart, pancreas and muscle. Lipotoxicity has roles in insulin resistance and pancreatic beta cell dysfunction. Increased circulating levels of lipids and the metabolic alterations in fatty acid utilization and intracellular signaling, have been related to insulin resistance in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
232
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(237 citation statements)
references
References 189 publications
1
232
0
4
Order By: Relevance
“…The reduction in lipogenesis observed with systemic dopamine agonist administration was coupled with a substantial increase in the protein turnover rate, and such an action is a major contributor to the resting metabolic rate. If adipose and non‐adipose tissue lipid stores are reduced as a result of energy flux away from lipid accretion and towards protein turnover, the adverse impact of the HFD on both body fat store level and insulin sensitivity (eg, via the facilitation of lipotoxicity) may be expected to be lessened, as observed in the present study. Such systemic dopamine agonist treatment also reduced elevated sympathetic tone, hypertension, hyperleptinaemia, and hepatic inflammatory and gluconeogenic activity, consequently reducing multiple components of insulin resistance syndrome.…”
Section: Discussionmentioning
confidence: 51%
“…The reduction in lipogenesis observed with systemic dopamine agonist administration was coupled with a substantial increase in the protein turnover rate, and such an action is a major contributor to the resting metabolic rate. If adipose and non‐adipose tissue lipid stores are reduced as a result of energy flux away from lipid accretion and towards protein turnover, the adverse impact of the HFD on both body fat store level and insulin sensitivity (eg, via the facilitation of lipotoxicity) may be expected to be lessened, as observed in the present study. Such systemic dopamine agonist treatment also reduced elevated sympathetic tone, hypertension, hyperleptinaemia, and hepatic inflammatory and gluconeogenic activity, consequently reducing multiple components of insulin resistance syndrome.…”
Section: Discussionmentioning
confidence: 51%
“…Numerous studies indicate that visceral obesity is the main cause of insulin resistance and MS [30]; nevertheless, the causes of reduced insulin sensitivity in the target organs are not exactly known. It is suggested that the common denominator of these metabolic disturbances may be redox imbalance as well as increased oxidative stress [31]. Moreover, despite the proven effectiveness of bariatric surgery, it is unclear whether it improves the redox homeostasis of morbidly obese cases.…”
Section: Discussionmentioning
confidence: 99%
“…JNK3 is only expressed in the brain, heart and testis [57,58]. In obese mice, increased lipid toxicity pressure activates JNK, and JNK activation leads to insulin resistance [59]. By comparing the effects of GSPE on lipid deposition in mice fed with a normal diet and high-fat diet, it was found that GSPE decreased the expression of FA synthase, C/EBPα protein and MPARγ peroxidase receptor mRAN, which are the lipid production-related genes, through inhibiting the JNK pathway effectively reduced fat deposition [60][61][62] and showed a dose dependency.…”
Section: Inhibiting the C-jun Aminoterminal Kinase Pathwaymentioning
confidence: 99%